PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) DALAM PEMBELAJARAN SENI TARI DI SMP NEGERI 3 BUKITTINGGI - Widya Damayanti; Fuji Astuti; Zora Iriani (FBS Universitas Negeri Padang, 2014)
Abstract Purpose of this research is to conduct cooperative learning method that is STAD to increase students` activities and students` learning outcomes in dance and art learning at Junior High School number 3 Bukittinggi (SMP Negeri 3 Bukittinggi). This research is kind of quantitative research using experimental technique. Instruments of this research are observation sheets of learning process and essay test. The data is analyzed by using t-test in order to see the differences between two groups. The result of the research shows that by using STAD cooperative learning method, students` activities and students` learning outcomes in dance and art learning are increased. In the pre data before the experiment, mean of second semester mid-term test in 2013/2014 period of teaching is 74,19. The mean in experimental group after STAD cooperative learning applied is 83,39, comparing to the mean in control group is 75,83. Keywords: Conventional, Cooperative, Randomized Control-Group Posttest Only Design, STAD, t test